Increased serum delta neutrophil index levels are associated with intrahepatic cholestasis of pregnancy. Issue 12 (16th September 2021) - Eroğlu, Hasan; Şahin Uysal, Nihal; Sarsmaz, Kemal; Tonyalı, Nazan Vanlı; Codal, Bahadır; Yücel, Aykan
Abstract: Objective: This study aims to compare the maternal serum delta neutrophil index (DNI) levels in intrahepatic cholestasis of pregnancy (ICP) and healthy pregnancies. Methods: This study consisted of a group of patients ( n = 40) diagnosed with isolated ICP who gave birth in our hospital and a control group ( n = 60) between December 1, 2015, and June 30, 2018. The diagnosis of ICP was made based on pruritus and elevated fasting serum bile acids and liver enzymes. Laboratory tests of both groups in the hospitalization process were retrospectively examined. Maternal and neonatal characteristics, pregnancy outcomes, and DNI values of the two groups were compared. Statistical analyses were performed using SPSS version 20. Results: Mean maternal serum DNI levels were significantly higher in women with ICP than in the control group (0.49 ± 4.8 vs –3.99 ± 3.02, p = <0.01). Receiver operating characteristic (ROC) curve analysis was used to define the DNI value where ICP can be best predicted. Conclusion: DNI, a new inflammatory marker, was found to be higher in women with ICP than in normal pregnancies.